Catalytic auto-oxidation of o-hydroxyphenylthiourea by Iridium(III): A photometric sensing platform for Iridium - A. Sunil; Ashish Deep Chettri; S. Jagadeeswara Rao (Chemistry of Inorganic Materials)
o-Hydroxyphenylthiourea (HPTU) undergoes oxidative dimerization to form a yellow-colored disulfide in the presence of Iridium(III), a process significantly enhanced by the activator 1,10-phenanthroline. This catalytic oxidation was monitored spectrophotometrically at 416 ​nm under ambient conditions, employing both tangent and fixed-time methods. The method's performance was optimized by investigating factors like pH, reagent concentration, temperature, and potential interferents. A linear relationship between the rate of reaction and Iridium(III) concentration was observed in the range of 0.001 ​ng–5.0 ​mg of Iridium per mL, enabling the detection of Iridium(III) down to 0.001 ​ng/mL at pH 11.7. The method's simplicity, cost-effectiveness, and sensitivity make it suitable for the determination of Iridium(III) in real-time samples, eliminating the need for additional reagents, complex procedures, or preconcentration steps.